Contemporary Management of Chronic Ear Disease. (23rd August 2013) - Isaacson, Brandon; Bojrab, Dennis I.; Bennett, Marc L.; Kaylie, David; Warren, Frank M.; Haynes, David S.; Smouha, Eric E.
Abstract : Program Description: This miniseminar will discuss various aspects of the management of chronic ear disease, including ossicular chain reconstruction, cartilage and pediatric tympanoplasty, the role of endoscopes, and the management of chronic otitis media without cholesteatoma. Time permitting, a discussion on the management of labyrinthine fistulas will also be presented. A case based approach to these topics will be presented by the moderators to the panel members. Educational Objectives: 1) Describe ossicular chain reconstruction, including approaches, staging, and prosthesis selection (including autologous materials). 2) Recognize indications and methods of cartilage tympanoplasty and pediatric tympanoplasty. 3) Manage chronic otitis media without cholesteatoma and the role of endoscopes in chronic ear surgery.